TEAL WING OWR Program, Semi-Annual Technical Report for Period Ending 30 September 1973 - Wagner, Robert B (1973)
Progress to date consists of the following: two of the three seasonal measurements of at-sea natural noise were made and partially analyzed; the suitability of existing, fleet-deployed antennas for the intended class of service was investigated; and, the channel characterization experiments, performed during August 1973 between Cape Cod and two points on the coast of Maine (100 and 220 nm) are described under the following categories: equipment, physical set-up, and some preliminary data results which indicate that dispersion is insignificant on the surface-wave mode for the environmental conditions prevailing during the test period. See also report dated 1 Apr 1973, AD759033.